Efficacy and safety analysis of new P2Y12 inhibitors versus clopidogrel in patients with percutaneous coronary intervention: a meta-analysis. (2nd December 2015) - Gan, Xue-Dong; Wei, Bao-Zhu; Fang, Dong; Fang, Qi; Li, Kai-Yong; Ding, Shi-Lan-Ying; Peng, Song; Wan, Jing
Abstract: Objective: New P2Y12 inhibitors, classified as oral (prasugrel and ticagrelor) and intravenous (cangrelor and elinogrel) drugs, have shown improved antithrombotic effects compared with clopidogrel in patients with acute coronary syndrome (ACS) or patients undergoing percutaneous coronary intervention (PCI) in landmark trials. The purpose of this study was to perform a meta-analysis of randomized trials that compared new P2Y12 inhibitors with clopidogrel to determine their efficacy and safety in patients undergoing PCI. Methods: Randomized controlled trials of at least 4 weeks, comparing new P2Y12 inhibitors with clopidogrel in PCI, were identified using the electronic databases Cochrane Central Register of Controlled Trials, Medline, PubMed, Web of Science, and Google Scholar from January 1, 1980, to July 31, 2014. Main outcome measures: The primary efficacy endpoints were all-cause death and major adverse cardiovascular events (MACEs). The primary safety endpoint was thrombolysis in myocardial infarction (TIMI) major bleeding. Results: Twelve studies including 71, 097 patients met the inclusion criteria. New P2Y12 inhibitors significantly reduced all-cause death (odds ratio [OR]: 0.81; 95% confidence interval [CI] 0.73–0.90, p  < 0.0001), MACEs (OR 0.81; 95% CI 0.73–0.90, p  < 0.0001), stent thrombosis (OR 0.58; 95% CI 0.49–0.69, p  < 0.00001), myocardial infarctions (OR 0.87; 95% CI 0.76–0.99, p  = 0.03) and cardiovascular death (OR 0.82; 95% CI 0.73–0.92, p  = 0.001) compared with clopidogrel. There were no significant differences between stroke (OR 0.87; 95% CI 0.72–1.05, p  = 0.14) and major bleeding events (OR 1.22; 95% CI 0.99–1.52, p  = 0.06) between the new P2Y12 inhibitor and clopidogrel groups. Conclusion: New P2Y12 inhibitors decreased death in patients undergoing PCI compared with clopidogrel with a considerable safety and tolerability profile; however, the risk/benefit ratio of ischemic and bleeding events should be further investigated.